Related factors and prognostic impact of cardiac valve calcification in maintenance hemodialysis patients - Chengjun WANG; Xiaorong BAO; Zixuan QIAO; Miao MIAO; Wei YE; Lizhen WANG; Zhengjia HE; Jiao WANG (Zhongguo Linchuang Yixue)
ObjectiveTo explore risk factors for cardiac valve calcification (CVC) in maintenance hemodialysis (MHD) patients and evaluate its impact on cardiovascular events and mortality. MethodsRetrospective selection of 223 patients with MHD admitted to the Department of Nephrology of Jinshan Hospital, Fudan University from June 30, 2019 to June 30, 2024, and enrollment completed within one week of June 30, 2019. Patients were divided into CVC and non-CVC groups. Baseline data and 5-year follow-up data were collected. The binary logistic regression analysis was performed to explore the risk factors for CVC. Kaplan-Meier survival curve was used to analyze the survival rate of patients. Cox proportional hazard regression model was applied to evaluate the impact of CVC on the survival rates of MHD patients. ResultsTotally, 223 MHD patients with an average age of (58.4±13.5) years and an average dialysis duration of (64.0±55.4) months were involved. Among them, 136(61.0%) were males, 117(52.5%) were complicated with CVC. Age, dialysis duration, diabetic kidney disease (DKD), the serum corrected total calcium and phosphate, intact parathyroid hormone (iPTH), high-sensitive C-reactive protein (hsCRP), and homocysteine (Hcy) were independent related factors for CVC (P＜0.05). Both all-cause mortality (46.6% vs 28.7%) and cardiovascular mortality (33.3% vs 16.0%) were significantly higher in the CVC group than those in the non-CVC group (P＜0.01). ConclusionsAge, dialysis duration, the primary disease, calcium and phosphate, and inflammation- and nutrition-related serum indicators are associated with CVC in MHD patients. CVC significantly increases mortality risk of MHD patients.